The Effect of Four Melhem\'s Empowerment Factors on the Empowerment of Staff in Hormozgan University of Medical Sciences, Iran - Manochehr Ghaseminejad raeini; Parvin Lakbala (Shahid Sadoughi University of Medical Sciences, 2023)
Background: The only sustainable competitive advantage of organizations is their employees. Capable and efficient manpower are the most important assets of organizations and communities. This will lead to sustainable development. The purpose of this study was to determine the effect of empowerment through four factors of ability (knowledge and skills, trust, motivation and communication) among the staff of Hormozgan University of Medical Sciences.  Methods: This was a descriptive study conducted in 2017.The statistical population consisted of 485 staff members of Hormozgan University of Medical Sciences. 215 people were selected by random sampling method. Then, the authors selected samples from each job category through stratified sampling method. To collect information, the authors used a standard empowerment questionnaire based on Melhem's model in addition to the demographic section. After distributing the questionnaire; t-student test and Spearman correlation were used to determine the status of research variables and also the type and extent of the relationship between them. Results: According to the results of t-student test, the average of all variables was more than 3 indicating the appropriate status of employees' capabilities. Moreover, the results of Spearman correlation test showed that the relationship between independent variables and dependent variables in this test was significant. All research hypotheses (main hypothesis and four sub-hypotheses) were confirmed. The results of the correlation coefficient of the relationship between knowledge and skill variables with empowerment showed a moderate intensity, while the correlation coefficient of the relationship between the variables of motivation, trust and communication with empowerment showed a low intensity. Conclusion: Due to the appropriate status of employees' empowerment, long-term empowerment programs are proposed to enhance employees' empowerment further.